DESIGN AND DEVELOPMENT OF CAMPUS ROOM USE MONITORING APPLICATION BASED ON ANDORID WITH MAGNETIC DOOR LOCK IN THE DEPARTMENT OF INFORMATICS AND COMPUTER ENGINEERING UNM - Nur Annisaa Badia; Zulhajji Zulhajji; Satria Gunawan Zain (Jurnal Media Elektrik, 2024)
The condition of campus room doors that are often open has the potential for misuse of campus rooms that do not comply with the schedule set in the room and affect the security of the room facilities. This research aims to produce an Android-based campus room usage monitoring application using magnetic door locks at JTIK FT UNM as well as knowing the results of functional testing and performance testing or system performance. This research uses the Research and Development method with the Rapid Application Development Development model with stages: needs analysis, system design, system building, validation, testing, and final product. The final product of this research is a system developed in an Android-based room usage monitoring application that is integrated with a magnetic door lock using the QR Code feature. In this case, the system utilizes the ESP32 microcontroller as a chip that receives and provides signals according to the program in the system. The test results obtained validation of the Android-based campus room usage monitoring application using magnetic door locks can be said to be valid and suitable for use.